2015
DOI: 10.1039/c4ra12523a
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolic nitrogen-doped carbon nanotubes: physicochemical properties, interactions with Pd and their role in the selective hydrogenation of nitrobenzophenone

Abstract: The selective synthesis of pyrrolic N-CNTs, which promote the catalytic activity, and selectivity of PdN/CNTs used to hydrogenate nitrobenzophenone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 80 publications
4
41
0
2
Order By: Relevance
“…2.2 and 1.2 nm), which performed extremely well in the selective hydrogenation of nitroarenes (Scheme 6) [65] and phenol [66] into the corresponding amines and cyclohexanone.A sf or the size effect, Nincorporation also exerts significant impact on the electronic state of the Pd NPs.N ie et al [67] found that the strong interactions between pyridinic Natoms and Pd species lower the reducibility of the metal, leading to the formation of ultrafine Pd clusters with ahigh percentage of Pd d+ and thus promoting the hydrogenation of the aromatic rings of phenol and benzoic acid (Scheme 7). Interestingly,N yamori et al [21] observed that the Pd 2+ /Pd 0 ratio increased as the amount of Scheme 5. Palladium-catalyzed partial reduction of 1,5-cyclooctadiene to cyclooctene.…”
Section: Catalytic Reductions 421 Hydrogenation and Transfer Hydromentioning
confidence: 99%
See 1 more Smart Citation
“…2.2 and 1.2 nm), which performed extremely well in the selective hydrogenation of nitroarenes (Scheme 6) [65] and phenol [66] into the corresponding amines and cyclohexanone.A sf or the size effect, Nincorporation also exerts significant impact on the electronic state of the Pd NPs.N ie et al [67] found that the strong interactions between pyridinic Natoms and Pd species lower the reducibility of the metal, leading to the formation of ultrafine Pd clusters with ahigh percentage of Pd d+ and thus promoting the hydrogenation of the aromatic rings of phenol and benzoic acid (Scheme 7). Interestingly,N yamori et al [21] observed that the Pd 2+ /Pd 0 ratio increased as the amount of Scheme 5. Palladium-catalyzed partial reduction of 1,5-cyclooctadiene to cyclooctene.…”
Section: Catalytic Reductions 421 Hydrogenation and Transfer Hydromentioning
confidence: 99%
“…Metal organic chemical vapor deposition (MOCVD) has also been developed for the fabrication of metal/nitrogen/carbon nanostructures from organometallic precursors. [21] During these processes,t he surface chemistry of the support plays avital role for the immobilization. In particular,incorporated Natoms endow the carbon atoms with increased basicity and hydrophilicity,f acilitating the deposition of sputtered metal atoms.I ng eneral, the impregnated metal salts are reduced further to the metallic state with H 2 .…”
Section: Synthesis Of Metal Nps Supported On N-doped Carbonmentioning
confidence: 99%
“…Therefore, the XPS spectra of palladium were investigated. In the inset of Figure , the Pd3d peaks are deconvoluted into two pairs of doublets: Pd3d 3/2 (∼340.9 eV), Pd3d 5/2 (∼335.9 eV) and Pd3d 3/2 (∼342.4 eV), Pd3d 5/2 (∼338.0 eV), assigned to Pd 0 and Pd 2+ , respectively . It can also be seen that Pd contains with two kinds of valence states in all the samples, except for the difference in the ratio of Pd 0 /Pd 2+ .…”
Section: Resultsmentioning
confidence: 92%
“…. Recently, the preparation of several N‐CNT‐based catalysts by immobilizing NPs onto N‐CNTs has been reported, and the synthesis of N‐CNTs is usually accomplished by the chemical vapor deposition (CVD) process …”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…[75] Recently, the preparation of several N-CNT-based catalysts by immobilizing NPs onto N-CNTs has been reported, and the synthesis of N-CNTs is usually accomplished by the chemical vapor deposition (CVD) process. [76,77] In 2017, Zhu and coworkers developed a new strategy to uniformly deposit Pd NPs on an N-CNT surface. [78] In their approach, a palladium NP-decorated N-CNT catalyst was obtained by the reduction of H 2 PdCl 4 and employed sodium dodecyl sulfate (SDS) as a salt and polyvinylpyrrolidone (PVP) as both a stabilizing agent and a surface modifier for the uniform dispersion of Pd NPs.…”
Section: Pd Nps Immobilized On Cntsmentioning
confidence: 99%